Using social network analysis to understand the impact of systems integration efforts: a case study from Thunder Bay - Rebecca Schiff; K. Arnold; A. Wilkinson (Cogent Social Sciences, 2024)
Over the past two decades Canadian municipalities have seen the emergence of formalised systems-level collaborative approaches to addressing homelessness and housing issues. The implementation of such approaches has been widespread and to some extent standardised by the Canadian (federal) government through the mandated formation of ‘community advisory boards’ (CABs) and their associated ‘Community Entities (CEs) which direct the use of federal homelessness funding’. CABs have significantly affected systems-level strategic planning to address homelessness in urban, rural, and remote areas across the country. These groups have had impact and success, but also face challenges related to effective collaboration and governance. Despite the significant influence of these groups – in directing funding and resources to address homelessness – there is little independent research on these groups, their effectiveness, the relationships that constitute CABs or the degree to which they achieve their stated goals of cross-sectoral integration. Social Network Analysis (SNA) is an approach for understanding networked organizational relationships. It has been used in some limited housing and homelessness scholarship to document the quantitative and qualitative features of networks and for understanding the comparative successes and impacts of these efforts. In the broadest sense, SNA can be described as the investigation of relationships among individuals and/or groups in order to identify and interrogate social structures. In this paper, we utilize a case study approach to explore how SNA might contribute to a better understanding of cross-sectoral network building in a CAB with the aim of enhancing systems-level planning to end homelessness.